2021
DOI: 10.21062/edp.2022.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Outdoor Education and Stay in Nature on Pupils 'Physical and Psychical Health

Abstract: The aim of this review study is to present the current state of pedagogical and psychological research in the field of outdoor education of primary school pupils (ISCED 1 & ISCED 2). The study seeks answers to three basic questions: i) What are the common characteristics of published studies devoted to the benefits of outdoor education of primary school pupils? ii) What benefits of outdoor education are monitored in these studies? iii) What conclusions did these studies reach in the context of the observed ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Knowing all of the research documented benefits of outdoor education (Kroufek et al, 2021) and the results of this study, the need for more in-depth training of primary school teachers in outdoor education and distance outdoor education can be pointed out. They should be exposed to it already during their studies and should also have the opportunity to study it in the framework of teacher training courses provided by both the state and NGOs.…”
Section: Discussionmentioning
confidence: 83%
“…Knowing all of the research documented benefits of outdoor education (Kroufek et al, 2021) and the results of this study, the need for more in-depth training of primary school teachers in outdoor education and distance outdoor education can be pointed out. They should be exposed to it already during their studies and should also have the opportunity to study it in the framework of teacher training courses provided by both the state and NGOs.…”
Section: Discussionmentioning
confidence: 83%
“…Research confirms that children should be given the opportunity to enjoy positive experiences with nature from an early age (Kellert 2002), as these direct experiences play an important role in developing positive beliefs, attitudes, and behaviors towards the environment (Tilbury 1994). Love for nature, as well as empathy for other living creatures, is already formed in the period of pre-school education (Wilson 1994) and it is desirable to further develop it during compulsory schooling (Kroufek et al 2021). Nisbet et al (2009) found that a close relationship with nature is directly proportional to the time spent in it.…”
Section: Introductionmentioning
confidence: 99%